2022
DOI: 10.1039/d1ob02118d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cu(ii)-based systems for C(sp3)–H bond functionalization: insights into the synthesis of aza-heterocycles

Abstract: Herein we report the synthesis of imidazo[1,5-a]pyridine heterocycles via a Cu(II)-mediated functionalization of α’-C(sp3)–H bonds of pyridinylaldimines and subsequent cyclization. This strategy exploits the inherent directing ability of heteroleptic aldimine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Very recently, M. Camats et al. reported the functionalization of pyridinylaldimine substrate with a catalytic approach employing copper bis‐pivalate and dichloro‐5,6‐dicyano‐1,4‐benzoquinone (as cyanating agent) obtaining imidazo[1,5‐a]pyridine‐1‐carbonitrile derivatives under microwave irradiation via a telescoped Cu‐catalyzed C(sp 3 )−H amination/cyclization followed by C(sp 2 )−H cyanation [58] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, M. Camats et al. reported the functionalization of pyridinylaldimine substrate with a catalytic approach employing copper bis‐pivalate and dichloro‐5,6‐dicyano‐1,4‐benzoquinone (as cyanating agent) obtaining imidazo[1,5‐a]pyridine‐1‐carbonitrile derivatives under microwave irradiation via a telescoped Cu‐catalyzed C(sp 3 )−H amination/cyclization followed by C(sp 2 )−H cyanation [58] …”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57] Very recently, M. Camats et al reported the functionalization of pyridinylaldimine substrate with a catalytic approach employing copper bispivalate and dichloro-5,6-dicyano-1,4-benzoquinone (as cyanating agent) obtaining imidazo[1,5-a]pyridine-1-carbonitrile derivatives under microwave irradiation via a telescoped Cucatalyzed C(sp 3 )À H amination/cyclization followed by C(sp 2 )À H cyanation. [58] In 2005 J. Wang et al reported a direct cyclization of 2,2'dipyridylketone with different aromatic aldehydes in the presence of ammonium acetate for the synthesis of impy skeleton as a useful ligand (see Scheme 7).…”
Section: Then He Pursued His Doctorate At the University Of Turin Whi...mentioning
confidence: 99%
“…[µ4-O{Cu(MeOH)}4Cl6] (737) / DMF Q [394] [µ4-O{Cu(3-nonyl-8-fluoroimidazo[1,5-a]pyridine)}4Cl6] (757) [µ4-O{Cu(MeCN)}4Cl6] (707), 3-nonyl-8-fluoroimidazo[1,5-a]pyridine / MeCN, 100 °C, 10 min Q [440] [µ4-O{Cu(Amt)}4Cl6] (758) [Cu(α-CgPAmtHMe)(Cl)][BF4], KHMDS / THF J [441] [µ4-O{Cu(nmp)}3(CuOH2)Cl6] (759) CuCl, O2 / nmp, H2O F [442] [µ4-O{Cu(Me2NH)}3{Cu(dmso)}Cl6] (760)…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…Imidazo [4,5-b]pyridines are principally studied for the development of emissive products for OLEDs (organic light-emitting diodes) and sensor applications due to their excellent emissive properties [23][24][25][26][27][28]. 4.…”
mentioning
confidence: 99%
“…Imidazo [4,5-b]pyridines are principally studied for the development of emi products for OLEDs (organic light-emitting diodes) and sensor applications d their excellent emissive properties [23][24][25][26][27][28]. 4. Imidazo [4,5-c]pyridines display a bioisosteric resemblance to the purine nuc manifesting similar structural and electronic properties.…”
mentioning
confidence: 99%